Species diversity of plankton as an indicator of water quality at sewerage disposal of several Industries In Surakarta . - WIRYANTO WIRYANTO; ARI SUSILOWATI; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2003)
The objective sof the research were to study the physical, chemist and biological (plankton) conditions of sewerage disposal from several lndustries In Surakarta, Physical parametert observed were temperature, total soluble solid and the texture of soli sediment, chemistry parameters observed were, includll